Determination of fructose in syrups by reverse flow injection spectrophotometry - Granda, Mayra; Serrano, María de los Angeles; Piña, Georgina; Díaz García, Marta Elena (Ciencia)
A reverse flow injection system is proposed for the spectrophotometric determination of fructose in symps based on the oxidation reaction of KiO4 with the sugar. The oxidant is injected in the sample channel and its consumption reflects the fructose content. The excess periodate reacted with a solution of KI introduced through a second stream. The iodine produced is measured spectrophotometrically at 350 nm or at 660 nm if starch is present. A linear calibration was obtained for 10 to 80 pg/mL fructose and the relative standard deviation was 1.3% for 40 pg/mL (n= 10). The detection limit found is 9 pg/mL. No significant interference was found from glucose, commonly present in most fructose samples. The proposed reverse FiA system was successfully applied to syrups with satisfactory precision. Sample throughput is 30 h-’.